EXPLORING EFL STUDENTS’ PROBLEMS IN LISTENING TO ENGLISH NEWS BROADCASTS - Zulfikar Zulfikar; Cut Tarri Aulia; Saiful Akmal (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
Listening is central for language learning and for daily communication. However, in foreign language learning, students still encounter problems in understanding listening materials. This present study is aimed to reveal the students’ problems in listening English news broadcasts. The subjects of this study were two classrooms at the Department of English Language Education at an acknowledged university in Banda Aceh. The samples were made of 50 students in their third semester. This study employed a quantitative analysis approach. A close-ended questionnaire was used as the instruments in collecting the data. The findings showed that the difficulties faced by the students in listening to English news broadcast were mainly caused by unfamiliar topics, unfamiliar vocabulary, different accents, fast speech rate, unintelligible pronunciation, difficulty in inference making, excessively long passages, complicated grammatical structure, as well as complex ideas.